Declining Proportion of Foreign Exchange Earnings from Tourism to Gross Domestic Product in Nepal - Sutihar, Deo Narayan (Janapriya Journal of Interdisciplinary Studies, 2017)
This article attempts to estimate annual declining trend of proportion of foreign exchange earnings from tourism to Gross Domestic Product (GDP) in Nepal and test the significance of declining trend of this ratio using time series data of 20 years from FY 1991/92 to FY 2010/11l. It has been that the declining trend of foreign exchange earnings from tourism to GDP ratio is significant. The inequality in the distribution of foreign exchange earnings from tourism to GDP ratio is tolerable. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 45-50